Evaluation of Diverse Substrate Utilization in Mushroom Cultivation: Enhancing Yield and Nutritional Quality (International Journal of Scientific Research in Science and Technology, 2025)
An introduction to mushroom cultivation and it is a vital component of a sustainable agriculture, providing significant economic, environmental and nutritional advantages. This study investigates the impacts of various substrates like paddy straw(T1), Sawdust(T2), Cocopeat(T3) on the yield and nutritional quality of Pleurotus ostreatus (oyster mushroom), Each substrate underwent a specific preparation process to optimise its suitability for cultivation. Proximate analysis was to evaluate moisture, ash, crude fat, crude fiber, crude protein, and carbohydrate content. Results shows that moisture content across the treatments range from 82.8% to 83.15%, reflecting the fresh nature of the mushrooms. T3 exhibited the highest ash content (13.6%), suggesting superior mineral composition, while T2 shows the highest crude fiber (15.46%) and protein content (1.34 mg/ml), indicating its nutritional advantages. T1 had the highest carbohydrate content (57.95%), contributing the energy yield. The uniform fat content (1%) across all samples aligns with the lipid levels typical of mushrooms. This study highlights the influence of substrate composition and cultivation conditions on the nutritional profile of oyster mushrooms, suggesting that straw is good for overall health-wise. Future research should focus on substrate modifications and the exploration of amino acid profiles to enhance the nutritional and commercial viability of oyster mushroom cultivation.